Evaporation induced 18O and 13C enrichment in lake systems: A global perspective on hydrologic balance effects. (1st January 2016) - Horton, Travis W.; Defliese, William F.; Tripati, Aradhna K.; Oze, Christopher
Abstract: Growing pressure on sustainable water resource allocation in the context of global development and rapid environmental change demands rigorous knowledge of how regional water cycles change through time. One of the most attractive and widely utilized approaches for gaining this knowledge is the analysis of lake carbonate stable isotopic compositions. However, endogenic carbonate archives are sensitive to a variety of natural processes and conditions leaving isotopic datasets largely underdetermined. As a consequence, isotopic researchers are often required to assume values for multiple parameters, including temperature of carbonate formation or lake water δ 18 O, in order to interpret changes in hydrologic conditions. Here, we review and analyze a global compilation of 57 lacustrine dual carbon and oxygen stable isotope records with a topical focus on the effects of shifting hydrologic balance on endogenic carbonate isotopic compositions. Through integration of multiple large datasets we show that lake carbonate δ 18 O values and the lake waters from which they are derived are often shifted by >+10‰ relative to source waters discharging into the lake. The global pattern of δ 18 O and δ 13 C covariation observed in >70% of the records studied and in several evaporation experiments demonstrates that isotopic fractionations associated with lake water evaporation cause the heavy carbon and oxygen isotope enrichments observed in most lakes and lake carbonate records. Modeled endogenic calcite compositions in isotopic equilibrium with lake source waters further demonstrate that evaporation effects can be extreme even in lake records where δ 18 O and δ 13 C covariation is absent. Aridisol pedogenic carbonates show similar isotopic responses to evaporation, and the relevance of evaporative modification to paleoclimatic and paleotopographic research using endogenic carbonate proxies are discussed. Recent advances in stable isotope research techniques present unprecedented opportunities to overcome the underdetermined nature of stable isotopic data through integration of multiple isotopic proxies, including dual element 13 C-excess values and clumped isotope temperature estimates. We demonstrate the utility of applying these multi-proxy approaches to the interpretation of paleohydroclimatic conditions in ancient lake systems. Understanding past, present, and future hydroclimatic systems is a global imperative. Significant progress should be expected as these modern research techniques become more widely applied and integrated with traditional stable isotopic proxies. Graphical abstract: Highlights: Evaporation induced fractionation significantly modifies lake source water δ 18 O. Evaporation causes 13 C enrichment in the dissolved inorganic carbon pool. Significant O and C isotopic covariation occurs in >70% of lake carbonate records. Evaporation impacts isotope proxy records even when covariation is absent. Multi-proxy methods reveal detail not achievable with traditional approaches.